5-HT3 receptor antagonists for the prevention of postoperative shivering: a meta-analysis. (December 2016) - Zhou, Chengmao; Zhu, Yu; Liu, Zhen; Ruan, Lin
Objective: We evaluated the efficacy of 5-HT3 receptor antagonists for the prevention of postoperative shivering. Methods: We searched PubMed, the Cochrane Library, EMBASE and Web of Knowledge to find randomized controlled trials (RCT) of 5-HT3 receptor antagonists for the prevention of postoperative shivering. Two researchers independently screened studies, extracted data, and assessed quality in accordance with the inclusion and exclusion criteria, and then conducted a meta-analysis using RevMan 5.2. Results: Ultimately, 14 RCTs that included 980 patients were included in the analysis. We found that: 1) the incidence of shivering was significantly lower in 5-HT3 groups than placebo groups (relative risk, [RR] = 0.48, 95% confidence interval [CI] 0.40 – 0.58); 2) there was no significant difference in the incidence of shivering between 5-HT3 groups and meperidine groups (RR = 0.89, 95% CI 0.60 – 1.34). Conclusion: 5-HT3 receptor antagonists appear to prevent postoperative shivering, with a broadly comparable efficacy to meperidine.